The licensing system under the Malaysian Moneylenders Act 2003 - Muhammad Arif, Afida Mastura (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
Moneylending business is a longstanding industry that had served consumers from various backgrounds in Malaysia. This industry is regulated by the Moneylenders Act 1951, which has gone through a major amendment in 2003. One of the main areas of reform is the licensing regime. Licensing identifies competent traders and excludes the incompetent and dishonest. The old licensing system was criticised of being too general, lenient and outdated. This article will examine and analyse the new licensing system to determine whether these weaknesses have been rectified.